Abstract Characteristic of the Class of Unitary Positional Algebras of Operations - Sokhats’kyi, F. M. (Ukrains’kyi Matematychnyi Zhurnal, 2002)
We find an abstract characteristic of the class of unitary positional algebras of operations, i.e., algebras that contain a complete collection of selectors.